Concept of “Legitimate Expectationsˮ of Foreign Investors in the International Investment Arbitration Practice - Ilia V. Rachkov (Московский журнал международного права, 2014)
Based on the practice of international investment arbitral tribunals this article outlines the notion of “legitimate expectations of investors”. This notion is not used in bi- is not used in biand multilateral international investment treaties of Russia. However, as follows from the practice of international investment arbitral tribunals, legitimate expectations of investors constitute an integral part of the standard of fair and equitable treatment of foreign investor by the state hosting foreign investments. Only if a state gives specific representations and warranties to the investor, this creates legitimate expectations of the investor. If the state failed to perform such representations and warranties, it will not meet legitimate expectations of the foreign investor and, therefore, violated its obligation to treat such investor fairly and equitably. This may trigger liability of such state under international law towards the foreign investor, should he fi le a claim against such state with an international investment arbitral tribunal.